Parameterising Maximum Tsunami Amplitude with Earthquake Moment Magnitude for Trans-Oceanic Tsunamis - Tjipto Prastowo; Asiyah Khoiril Bariyah; Latifatul Cholifah; Hilda Risanti (ASM Science Journal, 2022)
This study examines a relationship between earthquake size and maximum tsunami amplitude using large earthquakes of M_w> 7.5 that led to trans-Pacific and Indonesian tsunamis. The data were sampled from tide gauges or DART surface buoys for seven Pacific tsunamis (the 2006 Kuril, Russia, 2009 New Zealand, 2011 Tohoku-oki, Japan, 2013 Solomon Island, 2010 Maule, 2014 Iquique, and 2015 Illapel) and six Indonesian tsunamis (the 2004 Indian Ocean, 2006 Pangandaran, 2007 Bengkulu, 2010 Mentawai, 2010 Simeulue, and 2012 Northern Sumatera). We found that the size better scales with M_w instead of other measures when relating to the mean maximum amplitude η. The main finding for the trans-Pacific cases was that the M_w scale is a logarithmic function of the mean amplitude, M_w = 0.77 log η + 8.84, consistent with previous work. For the Indonesian events, it was found that M_w = 1.92 log η + 10.36, reflecting different tsunami dynamics in the Pacific and Indian Oceans. The apparent difference is thus attributable to differences in both the topographical complexity and tsunami directivity in the two oceans. This is vital as the results provide insight into the nature of tsunami propagation approaching shorelines hence useful for improved tsunami early warning.